Exhibitions at Kharkiv Art Museum in 1991–2001: Traditions and Innovations - Дяченко, Наталя (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2016)
The article investigates the changes of national culture in the period after independence declaration on the example of Kharkiv Art Museum. Representatives of the cultural sphere obtained principally new prospects and possibilities due to the transformation of politic and ideological system. The author draws a conclusion that the museum made the extensive contribution in the cultural life of Kharkiv in this period because in its activity the Kharkiv Art Museum focused on exhibitions representing social processes.